METHODS OF DETERMINING PASSENGER FLOW IN PUBLIC TRANSPORT - O’tkirov , Rustam; Baratov , Ilhomjon (SAMBHRAM XABARNOMASI, 2024)
Annotation. The article analyzes the importance of methods for determining passenger flow in improving the quality of urban public transport services and correctly organizing movement intervals. Various calculation methods have been used to study passenger flow, and these methods have proven effective in determining the number of vehicles on routes, selecting the correct movement intervals, and studying passenger flow. The more vehicles there are on a route and the shorter their movement intervals, the higher the quality of transport services provided to passengers.